Pharmacogenetic and safety analysis of cinacalcet hydrochloride in healthy Chinese subjects - Liu, Yang-Jie; Sun, Lu-Ning; Cheng, Zi-Ping; Qian, Yi; Ma, Zeng-Qing; Zhang, Xue-Hui; Zhang, Hong-Wen; Xie, Li-Jun; Yu, Lei; Yuan, Zi-Qing-Yun; Liu, Yun; Wang, Yong-Qing (Annals of translational medicine, 2020)
Our study aims to explore the effect of genetics on the pharmacodynamics (PD) and pharmacokinetics (PK) of cinacalcet in healthy Chinese subjects; to investigate the effect of dietary factors on cinacalcet, and to evaluate the safety of cinacalcet under fasting and non-fasting conditions using a bioequivalence trial. We investigated the relationship of cinacalcet PK with single nucleotide polymorphisms (SNPs) of CYP3A4, CYP1A2 and CYP2D6, and of cinacalcet PD with SNPs of calcium-sensitive receptors (CASR) and vitamin D receptors (VDR) in 65 healthy Chinese subjects recruited to participate in this study. Our study was a phase I, open-label, randomized, two-period, two-sequence crossover, a single-center clinical study designed under both fasting and non-fasting conditions to investigate the effect of dietary factors on cinacalcet. Plasma cinacalcet concentrations were analyzed using a validated HPLC-MS/MS assay. Clinical laboratory tests evaluated safety. Thirteen SNPs of CASR, VDR, and CYP genes were selected for pharmacogenetic analysis. CYP3A4 rs4646437 was found to be associated with the PK of cinacalcet under fasting conditions (P<0.01). Subjects carrying T alleles of rs4646437 appeared to metabolize cinacalcet poorly. The C and AUC of subjects in the non-fasting group were significantly higher (P<0.0001) than those in the fasting group. The T , CL/F, and Vd/F in the fasting group were significantly higher (P<0.0001) than those in the non-fasting group. In the fasting group, the geometric least square mean ratios (T/R) of the C and AUC were 109.89% and 105.33%, and the corresponding 90% CIs were 98.36-122.79% and 98.04-113.15%, respectively. In the non-fasting group, the T/R of the C and AUC were 100.74% and 99.09%, and the corresponding 90% CIs were 92.65-109.54% and 94.79-103.58%, respectively. All adverse events (AEs) were mild, and no serious adverse events (SAEs) occurred during the bioequivalence trial. Following our investigation, we reached the following conclusions: CYP3A4 rs4646437 may affect cinacalcet PK; the reference and test preparations of cinacalcet were bioequivalent under fasting and non-fasting conditions and were safe to use; and dietary factors had a significant effect on the PK of cinacalcet, in that exposure to the drug increased when cinacalcet was taken after eating.